2022
DOI: 10.1200/go.22.00215
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Adopting Hypofractionated Radiotherapy as a Standard of Care in Low-and Middle-Income Countries

Abstract: Licensed under the Creative Commons Attribution 4.0 License Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Similar studies have been completed in cancers of other disease sites, which have demonstrated similar toxicity profiles and comparable oncologic outcomes between shorter and longer radiation courses [86][87][88][89][90]. Additionally, these shorter courses of treatment have been associated with decreased costs to the healthcare system and improved access and convenience for patients [91]. One study evaluating the safety and efficacy of a hypofractionated pelvic radiotherapy approach in patients with endometrial cancer is RT-PACE [92,93].…”
Section: Studies With Clinical Endpointsmentioning
confidence: 88%
“…Similar studies have been completed in cancers of other disease sites, which have demonstrated similar toxicity profiles and comparable oncologic outcomes between shorter and longer radiation courses [86][87][88][89][90]. Additionally, these shorter courses of treatment have been associated with decreased costs to the healthcare system and improved access and convenience for patients [91]. One study evaluating the safety and efficacy of a hypofractionated pelvic radiotherapy approach in patients with endometrial cancer is RT-PACE [92,93].…”
Section: Studies With Clinical Endpointsmentioning
confidence: 88%
“…There is ongoing debate regarding the cost of MRIgART and the length of time spent on the treatment couch [ 33 ]. This work adds to the expanding evidence supporting the move to increasingly hypofractionated regimes due to the socio-economic benefits to hospitals and patients, with a reduction in travel costs, re-location costs, time off work and improved toxicity outcomes for patients [ 34 ]. Furthermore, treatment on the MRL negates the need for fiducial markers and radiation exposure secondary to cone beam CT or X-rays, meaning that, although treatment requiring fiducials and/or CT guidance may provide a safe approach to implementing CTV-PTV margin reduction, it remains invasive and with the associated risks [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not mandatory, certain prerequisites are recommended for safely implementing HRT. These include a linear accelerator (LINAC) for three-dimensional conformal radiation therapy (3DCRT), CT treatment simulation with sub-3 mm slice reconstruction, both forward and inverse treatment planning software, proper immobilization devices, a comprehensive QA protocol, and a team of well-trained radiation oncology professionals [16,[20][21][22].…”
Section: Required Minimum Infrastructure For Hypofractionated Radioth...mentioning
confidence: 99%
“…While these are the minimum standards for safely and adequately delivering HRT, the preferred treatment delivery method involves volumetric modulated arc therapy (VMAT) or intensity-modulated RT (IMRT) utilizing a minimum 6 MV beam, accompanied by onboard image guidance and motion tracking systems [16]. In addition, regardless of the chosen technique (3DCRT, IMRT, or VMAT), certain QA tasks should be performed more frequently than the standard LINAC QA guidelines of the Task Group 142 report [23].…”
Section: Required Minimum Infrastructure For Hypofractionated Radioth...mentioning
confidence: 99%
See 1 more Smart Citation